Предмет: Математика,
автор: nelliakopan15
помогите пожалуйста срочно
Приложения:
Ответы
Автор ответа:
1
Ответ:
-50,7
Пошаговое объяснение:
3(0,4х + у) - 6(3х - у) = 1,2х + 3у - 18х + 6у = -16,8х + 9у = 3( -5,6х +3у)
если х=5; у=3,7
3(-5,6•5+3•3,7)= 3(-28+11,1)= 3•(-16,9)= -50,7
Похожие вопросы
Предмет: Окружающий мир,
автор: ник13012005
Предмет: Английский язык,
автор: янезнаюответ
Предмет: Русский язык,
автор: alenaalena5
Предмет: Физика,
автор: КоролеваКЛ
Предмет: Английский язык,
автор: иринка244